Stability Indicating Analytical Method Development and Validation for the Estimation of Calcium Dobesilate in Bulk Drug Using RP-HPLC - Bedadurge, Ajay B. (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The aim of the study is to develop a simple, precise, accurate, linear, and rapid stability-indicating method for the separation and identification of degradation products and mass studies of calcium dobesilate (CAD) drugs used in the treatment of diabetic retinopathy and chronic kidney disease as per the International Conference on Harmonization’s (ICH) guidelines. Materials and Methods: The technique makes use of an isocratic mode, an Enable C18 Kromasil (250 × 4.6 mm; 5μ) column, and a reverse phase column. The optimal parameters for the method are the mobile phase of acetonitrile (0.1%), OPA in water (20:80), a flow rate of 1 mL/min, and a UV detector with a detection wavelength of 310 nm. Results and Discussion: Degradation was carried out and CAD was sensitive to base conditions. Structure elucidation of the forced degradation products was observed using liquid chromatography-mass spectrometry. CAD was found to be stable under thermal, photolytic, acid, and peroxide conditions. Two degradation products were reported, but we did not get the m/z of degradation products of CAD. We report these degradation products as unknown impurities. The suggested procedure was validated in accordance with ICH Q2 (R1) standards. Accuracy studies were observed that the percentage recovery was found to be 98.0–102.0% and the linearity of the method was excellent over the range of 80–120 μg/mL. Relative standard deviations of 0.612% demonstrate the precision. The results showed that the limits of detection and quantitation were, respectively, 0.477 and 1.445 ug/mL. Conclusion: According to validation and degradation results, the method was found to have good stability, indicating its nature as well as being user-friendly